Kinetics of Proton Binding to the Sarcoplasmic Reticulum Ca-ATPase in the E(1) State - Fibich, Andreas (The Biophysical Society, 2007)
A new caged proton, 2-methoxy-5-nitrophenyl sulfate, was synthesized and used in time-resolved pH jump experiments to study proton binding in the sarcoplasmic reticulum Ca-ATPase. The major advantage of this compound is that it does not produce significant artifacts in experiments in which the fluorescent styryl dye 2BITC is used to monitor ion movements in the Ca pump. Two rate-limiting processes were resolved and their dependence on pH, Ca(2+) concentration, and temperature investigated. The faster process showed a relaxation time between 4 and 8 ms independent on pH and Ca(2+) concentration, and the time constant of the slower process varied between 31 ms (0 Ca(2+)) and 100 ms (100 μM Ca(2+)). A consistent mechanism to explain the results was derived in agreement with previous studies and the generally accepted Post-Albers scheme of the pump cycle. This mechanism requires that under physiological conditions the ion-binding sites are always occupied and two protons and a Ca(2+) ion replace each other. In the absence of ATP at low pH a nonphysiological state can be induced in which up to four protons bind to the Ca pump in the E(1) conformation. So far it could not be verified whether these additional protons bind to amino acid side chains or are coordinated as hydronium ions.